2014
DOI: 10.1177/1098612x14538873
|View full text |Cite
|
Sign up to set email alerts
|

Utility of feline coronavirus antibody tests

Abstract: Eight different tests for antibodies to feline coronavirus (FCoV) were evaluated for attributes that are important in situations in veterinary practice. We compared four indirect immunofluorescent antibody tests (IFAT), one enzyme-linked immunosorbent assay (ELISA) (FCoV Immunocomb; Biogal) and three rapid immunochromatographic (RIM) tests against a panel of samples designated by consensus as positive or negative. Specificity was 100% for all but the two IFATs based on transmissible gastroenteritis virus (TGEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 20 publications
0
41
0
4
Order By: Relevance
“…These 21 samples with conflicting results are likely to be true positive since an IIF-negative result could be related to antibody sequestration by high viral loads (Meli et al, 2013). In addition, Addie et al (2015) demonstrated that up to 43% antibodypositive effusions from FIP cases were negative for FCoV RNA, likely as a consequence of PCR inhibition by interfering substances or RNA degradation during sample transportation and storage. However, in the absence of alternative diagnosis, even those 5 cats with neither FCoV antibodies nor RNA in their effusions could not be definitively considered as non-FIP animals (Addie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These 21 samples with conflicting results are likely to be true positive since an IIF-negative result could be related to antibody sequestration by high viral loads (Meli et al, 2013). In addition, Addie et al (2015) demonstrated that up to 43% antibodypositive effusions from FIP cases were negative for FCoV RNA, likely as a consequence of PCR inhibition by interfering substances or RNA degradation during sample transportation and storage. However, in the absence of alternative diagnosis, even those 5 cats with neither FCoV antibodies nor RNA in their effusions could not be definitively considered as non-FIP animals (Addie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Addie et al (2015) demonstrated that up to 43% antibodypositive effusions from FIP cases were negative for FCoV RNA, likely as a consequence of PCR inhibition by interfering substances or RNA degradation during sample transportation and storage. However, in the absence of alternative diagnosis, even those 5 cats with neither FCoV antibodies nor RNA in their effusions could not be definitively considered as non-FIP animals (Addie et al, 2015). Unfortunately, clinical cases were mostly untraceable and confirmatory necropsy was not done in any case, so that the lack of confirmatory testing represents the main limitation of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The antibody titers were tested by IFA in 49 cats and, on the scale proposed by Addie et al ( 17 ), were ranked from high positive (400–1,280; n = 13) to very high positive (>1,280, n = 36); 10 of the 49 had titers > 12,800. In the two cats with low positive titers (100), the diagnosis was confirmed by immunostaining of biopsied lesions for the FCoV antigen.…”
Section: Resultsmentioning
confidence: 99%
“…One quick way to establish whether that was possible is to look at the incubation period: from first becoming infected with FCoV to the development of FIP takes at least 3 weeks, so if a cat has been spayed, then is noticed to have an effusion a week later when the stitches are being removed, she must have been already infected prior to the operation. (Addie, Le Poder, et al, 2015). Because many pedigree kittens will have antibodies to FCoV, if may be preferable to offer a pre-operation RT-PCR test to establish if a cat is actually shedding FCoV.…”
Section: Did My Cat Catch Fcov/fip In Your Practice?mentioning
confidence: 99%